Language Choices and Language Attitudes of Indonesian College Students: A Case Study at Universitas Dian Nuswantoro Semarang (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to discover language choices of third year English students at Udinus in following domains: settings, participants, and topics as well as to examine those students' attitudes to Javanese. The study used descriptive qualitative method since it focused on examining the respondents to gain profound information from them. The data were collected through the questionnaire consisting of questions about the respondents' backgrounds, language choice and language attitudes to Javanese language. Language attitudes are measured with likert scale composed answers from strongly disagree, disagree, neutral, agree, and strongly agree. The questionnaire was distributed to 20 English students of third year of Udinus who are able to speak Javanese or were born and live in one of the cities in Javanese-speaking provinces. The data were analyzed using descriptive method. It was meant to describe and interpret the data descriptively. The findings revealed the use of mix of Javanese and Indonesian and Indonesian itself are more popular in the most parts of domains due to factors of social dimensions; however, overall the respondents show favorable attitudes to Javanese. It can become input and output for related institutions to make sure its sustainability and its rising by producing program.